Keep on planting! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Joseph Feulefack, coordinator of the Forest Tree and Environment Club in Kumba, south-west Cameroon tells us of FOTEC s work in creating an arboretum of trees as a teaching aid for schools. Since 1994 'more than 3000 trees were planted, from 33...